INHERENT FRAUD RISK ASSESSMENT: ANALYSIS OF MAIN TASKS TO MINIMIZE FRAUD RISK (Case Study of an Industrial Supervisory in Indonesia) - Yulia Nurlita; Edward Tanujaya (Association of Certified Fraud Examiners Indonesia Chapter, 2019)
This research aims to analyze and provide views on inherent fraud riskof an Industrial Supervisory in Indonesia. The inherent fraud risk analysis will be examined using fraud risk assessment methods presented in COSO: 2016.Based on observations of the main tasks and work units of the organization, there are 18 fraud schemes identified.The results of this study indicate that the four highest fraud schemes are